Elimination of structural deficits using the Joint Task of “Improving the regional economic structure”: A comparison of the structural policy in East Germany - Titze, Mirko (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
The Joint Task of “Improving the regional economic structure” is one of the most important instruments for the “Reconstruction East”. Herein the federal states have an extensive flexibility to define their own kind of industrial policy. Due to their structural deficits this paper is focused on the federal states in East-Germany. A decrease in the budget constrains the governments to improve efficiency of subsidies. However, there is one way to solve this problem: change unselective government aid to regional as well as sectoral government aid. This paper shows that there is no federal state, which has applied this kind of policy forcefully.